ELECTROPLATING DRYING TIME MINIMIZATION THROUGH BOLT DRYER MACHINE - Galang D.K, Antonius; Wikantyasa, Arya Sena; Bagaskara, Johannes Christian; Kumbarasari, Shanti; Wibowo, Yohanes T. (AUSTENIT, 2022)
One of the steps after the electroplating/coating process on the product is the drying process. In Micro, Small and Medium Enterprises, the drying process on CIV KG 0741 bolts with a diameter of 10 mm and a length of 20 mm requires a drying time of 6 hours. Drying simply and naturally has limitations, requiring a large drying area depending on the weather, time and temperature, which cannot be controlled. A simple automatic dryer is needed using a single-phase electric power source and simple and ergonomic maintenance methods to obtain a quality product with a measurable drying duration. Design and analysis of drying on the dryer. The dryer with dimensions of 680 x 480 x 967.12 mm3 has a mass of 21.94 kg with a drum capacity of 20 kg. The motor propulsion used is 1 HP, 5.08 Nm of torque and capable of rotating at 1500 rpm with an effort of 39296.66 Joules. The dryer can dry as much as 20 kg of bolts in 5 minutes faster than solar energy, with a drying time of 15 minutes to 1 hour.